Attitudes of college students toward developmentally disabled peers - Turner, Robert W. (Robert William), 1952-
The central purpose of this study was to examine the attitudes of non-disabled college students toward their developmentally disabled peers attending the same college. Specifically, it examined the attitudes of non-disabled students toward the developmentally disabled students in the Transitional/Vocational Program the Fairview campus of Fairview College, Alberta, Canada. Objectives included: 1) to review literature related to attitudes toward the developmentally disabled, 2) to identify and to present to the students an instrument to assess attitudes toward developmentally disabled adult students, and 3) to analyze the results by comparing selected groups of students to each other, by certain demographic variables and to the norms established for the instrument. Information received from the respondents was analyzed using analysis of variance and t-tests. Based on the data collected and the review of the literature, the following conclusions and recommendations were made: Conclusions: 1. From the review of the literature it is apparent that attitudes toward the developmentally disabled are often less than favorable. 2. Non-disabled students at Fairview College appear to regard their developmentally disabled peers as significantly different from themselves and that this difference is of a negative valence. 3. The developmentally disabled students apparently hold a significantly more positive attitude towards themselves than that held by their non-disabled peers towards the developmentally disabled at Fairview College. This finding supports previous research in this area. The A.T.D.P. authors have established separate and more positive norms for the disabled. Recommendations: I. Post-secondary institutions that provide special training programs for the developmentally disabled should examine the attitudes of important associational groups within the college community. 2. A comprehensive intervention should be designed and instituted where required, that is targeted at improving the attitudes of the non-disabled ...